Surgical treatment of the initial stages of progressive keratoconus in children - S.B. Izmailova; E.Yu. Markova; A.Z. Ciganov; L.L. Arutyunyan (Офтальмохирургия)
Introduction. The review presents the current data on the methods of surgical treatment of the initial stages of keratoconus in children, the possible manifestation of keratoconus as one of the symptoms of undifferentiated connective tissue dysplasia, as well as possible methods of prevention of the disease progression. Purpose. To present current literature data regarding surgical treatment of the initial stages of progressive keratoconus in children. Material and methods. For the review the literature sources were searched through the abstract databases PubMed and Scopus for the period up to and including 2022 using the following key words: ICRS, corneal collagen crosslinking, Keratoconus, connective tissue dysplasia. A total of 51 articles relevant to the review topic were selected. Results. Numerous studies have confirmed the effectiveness of timely surgery for the initial stages of keratoconus in improving the anatomical and functional outcomes of treatment of various diseases. However, even timely and perfectly performed surgery for progressive keratoconus may have different consequences depending on the degree of connective tissue dysplasia. Conclusion. The performed analysis of the literature allows to claim that keratoconus in children should be considered as a pathology related to the disturbance of structures and organization of collagen matrix of the whole body. It is also necessary to note that treatment tactics should be determined individually and be based on the age and values of comprehensive special examination of each particular child.